â€œANALISIS UJI LAIK FUNGSI JALAN BERBASIS SISTEM INFORMASI GEOGRAFISâ€ (Studi Kasus : Ruas Jalan 40 kota Sofifi) - Zainudin, Zainudin; Gaus, Abdul; Rauf, Ichsan (Program Studi Teknik Sipil, Universitas Khairun, 2023)
Kilometer 40 of Sofifi City needs to be analyzed regarding the feasibility of road functions by monitoring and evaluating its technical standards because it is located in a special area for the government center so that access to land transportation increases and can reduce the level of feasibility of road functions. Analyze the feasibility of road functions on each segment of the Kilometer 40 road in Sofifi City and map the feasibility of road functions on the Kilometers 40 road in Sofifi City by using Arc Gis. The result technically for the section of km 40 Sofifi City, from a total of nine (9) segments, it can be determined that the road section has a